Lógicas institucionais e estratégia como prática: um estudo em organizações constitutivas do campo da cachaça de alambique - Paiva, André Luiz de (2017)
Cachaça is a genuinely Brazilian alcoholic drink. The production and consumption of artisanal cachaça, an variant of this spirit, is involved in a plurality of meanings, practices and actors that constitute a social field whose origin refers to the colonial period. Specifically the state of Minas Gerais has the largest quantity of cachaça producers in the country. Among these, a group has articulated since the 1980s, representing a movement of re-signification of the symbolic and material dimensions of the drink, characterized by the distinction of practices seeking recognition of the spirit in front of the State and classes of greater purchasing power. Based on constructivist assumptions applied to the perspectives of the Strategy as Practice (SAP) and the institutional logics, we understand that these subjects are articulated in organizations and through their daily practices build strategies. These practices are constituted by a set of activities inserted in a macro institutional context in which they appear institutions and their respective logics, or action patterns based on material practices and symbolic systems. Thus, considering theoretical and empirical gaps, our main objective in this dissertation was to understand the influence of multiple institutional logics in the construction of strategy as practice in organizations producing cachaça located in Minas Gerais. Based on specific objectives, we have prepared three scientific articles. In the first paper, we discuss contributions from the perspective of institutional logics to the study of SAP. In this direction, we constructed a research protocol in which we explore theoretical categories of these approaches and how subjects interpret the orientations of the logics in a context of institutional pluralism. In the second article, we investigated the configuration of the institutional logics that constitute the field of artisanal cachaça in Minas Gerais. Through bibliographic research, documentary and primary data, we identify and describe four logics that exert greater influence in organizations: tradition logic, state logic, market logic and technical-scientific logic. In this research, we highlight how these logics interrelate. On the other hand, in the third article, we used the elaborated research protocol and developed a multiple case study in organizations of artisanal cachaça located in Minas Gerais. We define three organizations whose profiles of strategists characterize them as belonging to the movement of re-signification of the consumption and production of artisanal cachaça. Thus, based on interviews, observations and documentary research, we describe the trajectories and repertoires of practitioners in each organization and the constitutive practices of production strategies and market insertion. In our analysis, we sought to understand how strategists constructed the practices and produced meanings from interpretations of hybrid orientations of the institutional logics of the field in their praxis. We observed that although there are similarities between the activities performed in the organizations, the meanings a ttributed to them vary according to the repertoires of the strategists and their interpretations regarding the institutional context. These results contribute to SAP studies in Brazil and corroborate discussions about institutional pluralism and practitioners' action.